O planejamento da atividade econômica como dever do estado - Adri, Renata Porto (2007)
This thesis is grounded on the uneasiness that throughout an entire academic path has gradually established the driving elements to the pursuit of knowledge. Based on the assumption that planning is a matter of Law, we focused on the article 174, caput, clause 1 of the 1988 Federal Constitution, analyzing the subject as it was undoubtedly set as necessary and intrinsic to the economic activity. The work was carried out by the aid of a bibliography comprehending renowned authors and scholars on this matter. This work was based on the assumption that there would be a semantic mistake in the understanding of the referred constitutional article. Therefore, the object of this study is: economic planning as a necessary action to the definition of the state s policies, bounding its existence to the constitutional text and analyzing how its absence can cause the implementation of improper public policies, due to its inefficiency or to its negligence. In order to develop this study, the political, social and economic scenario was developed, in which planning should seek its aim, not as a mere choice of the State, but as a duty of the State. Economic planning is not an isolated action. It implies an effort to set goals, gather resources and time, aiming desirable results for the welfare of society. To set feasible plans is a way of marching towards life in the Democratic Rule of Law. The explanatory memorandum that draws planning guidelines is an instrument that allows evaluation of the actions performed by the involved agencies and entities as well as their relating functions, making it possible for the Judiciary to control them. During the studies, a fact rose incontestable: the creation of regulatory agencies, within the Brazilian legal framework, is due to a political urge as a result of the lack of an effective, efficient and efficacious economic planning. By the end of the research, it was verified that the regulatory system, through the actions of the regulatory agencies, does not offer the assurances of universality and transparency. In short, this thesis puts foward a new view on the article 174, caput, clause 1 of the 1988 Federal Constitution, in the hope of achieving effectively the constitutional and legal rules, having as ideal a more fair and humanized democratic society